Speaking, listening and understanding : debate for non-native-English speakers - Rybold, Gary (International Debate Education Association, 2006)
"Speaking, Listening and Understanding is the first text designed specifically to introduce debate to new English language speakers. Written in clear, easily accessible prose, it presents the basics of debate while avoiding the complexity and excessive cultural references that make standard texts difficult for this audience to use."--Jacket.